ONCE UPON A TIME THERE LIVED A ROYAL COUPLE…: SILESIAN FAIRY TALES ABOUT PRINCESSES, DRAGONS AND… - Olszewska, Bożena (Literatura Ludowa. Journal of Folklore and Popular Culture, 2017)
The characteristic features of Silesian fairy tales are their democratic nature and ideological layer, both of which are obviously a result of the complicated history of this region (Germanization, social exploitation of the common people). Understandably, young readers are not likely to find these political contexts and nuances of interest as they expect fairy tales to offer an engaging plot full of adventures, play and even humor. This causes the fairy tale to become affiliated with other folk genres (e.g. the legend) or the historical novel. These links are especially conspicuous in making the space, time and characters very concrete: the character has a name and performs the profession characteristic of this geographical region. The traditional fairy tale refers to an undefined time and place and leaves the charter considerably undefined. The authors of Silesian tales do not always follow the rules of the genre closely. They refer to folkloristic, regional, mythical and religious sources coming from ancient times until today. They also use international tropes and motifs (the lost princess, the dragon, the magician’s apprentice, the beauty and the beast, the prince transformed into an animal, magical objects), which they imbue with the local color for educational purposes and, perhaps, to meet the young reader’s expectations.